Measuring of social returns by South African impact investors - Ntombela, Nelisiwe (Graduate School of Business (GSB), 2025)
There is vagueness in measuring the social returns of impact investments. This creates uncertainty for investors on the impact that the investments have on the socio-economic environment in South Africa. There is no standard measurement metric, and this casts doubt on the quality of the impact data reported. This may hamper South Africa's potential to benefit from the positive effects of impact investments. This dissertation sought to understand the social returns measurement instruments within the South African impact investment landscape and explore the factors that influence their utility. The study was exploratory and qualitative in nature undertaking a thematic analysis of interview data from 11 impact investment practitioners in institutions in South Africa. From the analysis of the interview data, the prevalent measurement instruments within the impact investment landscape in South Africa can be categorised into frameworks, performance indicators, and monitoring and evaluation methods. The findings also revealed that there is no single measurement standard for impact investments in the South African context. Furthermore, the study revealed the subjectivity of social returns, inconsistent and weak reporting standards, inadequate measurement metrics, and a lack of established standards as the main themes when looking at the factors influencing the utility of measurement instruments. Finally, the measurement of social returns can be improved by assigning monetary value to impact, optimisation of measurement through technology, ESG integration and value-driven decision-making, narrative-based impact reporting, and external validation and accounting. Based on the findings of the study, the author recommends the establishment of a single customised measurement tool that incorporates performance indicators of SDGs and ESGs be adopted in the South African impact investment context and that more research should be undertaken on the use of technology to track and report impact data.